2020
DOI: 10.1155/2020/7049812
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Underlying Mechanism of Eucommiae Cortex against Osteoporotic Fracture by Network Pharmacology

Abstract: Background. Du Zhong (DZ), or Eucommiae Cortex, a traditional Chinese herbal medicine, has been used to treat osteoporosis. Although it has been reported that DZ can improve bone mass in ovariectomized rats, its pharmacological mechanisms in treating osteoporotic fractures (OPF) remain unclear. Methods. In this study, we used a network pharmacological manner to explore its potential complicated mechanism in treating OPF. We obtained DZ compounds from TCMSP and BATMAN-TCM databases and collected potential targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Mi et al [35] displayed that miR-7223-5p suppressed proliferation and fostered apoptosis of osteoblasts via targeting PIK3R1. Shuai et al [36] displayed that PIK3R1 may be a key target of Eucommiae Cortex for osteoporosis by network pharmacology. As such, our findings revealed that downregulation of PIK3R1 is associated with decreased proliferation and augmented apoptosis of osteoblasts, while its upregulation has an opposite effect.…”
Section: Discussionmentioning
confidence: 99%
“…Mi et al [35] displayed that miR-7223-5p suppressed proliferation and fostered apoptosis of osteoblasts via targeting PIK3R1. Shuai et al [36] displayed that PIK3R1 may be a key target of Eucommiae Cortex for osteoporosis by network pharmacology. As such, our findings revealed that downregulation of PIK3R1 is associated with decreased proliferation and augmented apoptosis of osteoblasts, while its upregulation has an opposite effect.…”
Section: Discussionmentioning
confidence: 99%
“…e bioactive ingredients and potential targets of five herbs in WSP were obtained in the online Bioinformatics Analysis Tool for Molecular mechANism of TCM (BATMAN-TCM, http://bionet.ncpsb.org.cn/batmantcm/) database [25]. e screening conditions were set at a score cutoff � 20, p < 0.05 [26,27]. BATMAN-TCM is a bioinformatics analysis tool for the molecular mechanism of TCM with abundant herb-ingredient-targetdisease association information and integration analyses of targets, which can help researchers comprehensively and systematically understand the ingredients and targets of TCM preparations.…”
Section: Step 1: Prediction Of Wsp In the Treatment Of Goutmentioning
confidence: 99%
“…[17] Bioinformatics, which includes herbal network pharmacology, continues to use an a priori analytical method to investigate the connections between medications, chemicals, disorders, and targets. [18] Network pharmacology is frequently used to clarify the mechanism of action of herbal medicines since it has the ability to analyze multiple components, multiple targets, and multiple pathways of herbal medicines, giving researchers new ideas and approaches. In order to identify the essential genes and pathways of DHJSD for the treatment of IVDD, as well as the active DHJSD compounds, we will apply the network pharmacology technique in this study.…”
Section: Introductionmentioning
confidence: 99%